Polyphenol‐Sensitized Atomic Layer Deposition for Membrane Interface Hydrophilization. (16th February 2020) - Yang, Xiaobin; Sun, Pan; Zhang, Huiru; Xia, Zijing; Waldman, Ruben Z.; Mane, Anil U.; Elam, Jeffrey W.; Shao, Lu; Darling, Seth B.
Abstract: Improvements in energy–water systems will necessitate fabrication of high‐performance separation membranes. To this end, interface engineering is a powerful tool for tailoring properties, and atomic layer deposition (ALD) has recently emerged as a promising and versatile approach. However, most non‐polar polymeric membranes are not amenable to ALD processing due to the absence of nucleation sites. Here, a sensitization strategy for ALD‐coating is presented, illustrated by membrane interface hydrophilization. Facile dip‐coating with polyphenols effectively sensitizes hydrophobic polymer membranes to TiO2 ALD coating. Tannic acid‐sensitized ALD‐coated membranes exhibit outstanding underwater crude oil repulsion and rigorous mechanical stability through bending and rinsing tests. As a result, these membranes demonstrate outstanding crude oil‐in‐water separation and reusability compared to untreated membranes or those treated with ALD without polyphenol pretreatment. A possible polyphenol‐sensitized ALD mechanism is proposed involving initial island nucleation followed by film intergrowth. This polyphenol sensitization strategy enriches the functionalization toolbox in material science, interface engineering, and environmental science. Abstract : A facile polyphenol dip‐coating sensitization strategy is presented for atomic layer deposition (ALD) to boost membrane interface hydrophilization engineering. Theoretical simulations and calculations are conducted for the sensitization mechanism. The resultant tailored membrane exhibits outstanding crude oil repulsion. The polyphenol‐sensitized ALD strategy will contribute to material science, interface engineering, and functionalization nanotechnology for clean water technology and beyond.